Unconventional monetary policy and productivity Evidence on the risk-seeking channel from US corporate bond markets - Albrizio, Silvia (OECD Publishing, 2019)
We examine the relationship between lax monetary policy, access to high-yield bond markets and productivity in the US between 2008 and 2016. Using monetary policy surprises, obtained from changes in interest rates futures in narrow windows around FOMC announcements, we isolate the increased access to high-yield bond markets relative to investment-grade bond markets that is due to unconventional monetary policy (UMP). We find that through the risk-taking channel, UMP has increased investors' appetite for high-yield US corporate bonds, thereby increasing access to high-yield bond markets for firms with a higher risk profile. Since the relationship between credit ratings and firm-level productivity is U-shaped, the aggregate effect on productivity is a priori unclear. Turning to the real economy, we thus analyse whether this additional access to finance had an effect on aggregate productivity by altering the reallocation of resources across firms. Our results show that unconventional monetary policy induced less investment in tangible capital by high-productive firms. However, before drawing conclusions on the net effects of UMP on aggregate productivity, we discuss a number of issues that this paper could not deal with due to data limitations, including prominently whether this apparent misallocation may have been offset by a shift in the composition of investments towards more intangible investment
Keywords: Science and Technology; Economics; United States